Collaborative Learning with Read Aloud Model In Supporting Reading Literacy In Elementary School - Istikhoroh Nurzaman, (International Conference on Elementary Education, 2024)
This study based on base urgency in creat undestanding to text presented. Research objectives this for produces a collaborative interactive read aloaud learning model as effort for create understanding to text. The model applied includes: 1) Designing; 2) Forming; 3) Facilitating; 4) Evaluating. Study this done with adapting McKenny & Reeves via stages procedure study EDR development which includes: 1) Identification Problem; 2) Design and Constraction; 3) Evaluation and Reflection. Data collection techniques were carried out with interview and observations. As for the subject research conducted_involving teachers and students of SDN Karangsambung, Tasikmalaya City. Conclusion from study this show that the collaborative read aloud model can implemented in learning read for support understanding read student school basic.